2020
DOI: 10.3390/ijerph17228514
|View full text |Cite
|
Sign up to set email alerts
|

Creating Short-Term Volume Flexibility in Healthcare Capacity Management

Abstract: It is well-known that unpredictable variations in supply and demand of capacity in healthcare systems create the need for flexibility. The main tools used to create short-term volume flexibility in the healthcare system include overtime, temporary staff from internal calling lists, moving staff across units, internal staffing pools, external staffing agencies, queuing patients, and purchasing care from external providers. We study the creation of short-term volume flexibility in healthcare systems to manage sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Table 1 contains four studies that analyze and discuss strategies to reduce waiting lists in non-surgical settings. These studies concern a variety of contexts in different countries, including primary care ( 16 , 18 ), outpatient clinics ( 17 , 18 ), hospital units ( 18 ), and imaging and radiology ( 19 ), and were conducted mostly before the COVID-19 pandemic ( 16 18 ). We observed that pre-COVID studies tend to perform deeper analysis and evaluations compared to post-COVID studies, in particular through data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 contains four studies that analyze and discuss strategies to reduce waiting lists in non-surgical settings. These studies concern a variety of contexts in different countries, including primary care ( 16 , 18 ), outpatient clinics ( 17 , 18 ), hospital units ( 18 ), and imaging and radiology ( 19 ), and were conducted mostly before the COVID-19 pandemic ( 16 18 ). We observed that pre-COVID studies tend to perform deeper analysis and evaluations compared to post-COVID studies, in particular through data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…One tool to address capacity shortages and increase operational exibility is to redeploy staff between units where they are quali ed to work, which requires a prior training process. For this, it is imperative that the types of services that can most bene t from such an approach are identi ed 35 . Sta ng plans that use exible deployments with a su ciently high number of staff are able to cope with peaks in demand and are cost-effective, as additional staff can contribute to units that require it 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The focus on the imbalance between flexible and fixed resources has been explored mainly in theoretical terms for its implications for the performance of health-care services. For example, it has been argued that in a situation where the level of the demand exceeds the capacity of hospitals to deliver health-care services, organizational efficiency will depend on the capacity to protect internal routes with a buffer of focused resources and to proactively deploy flexible resources using various routes according to the type of excess demand [ 28 ].…”
Section: Theoretical Considerations: Flexible Responses In An Ever-ch...mentioning
confidence: 99%
“…This is evident because although reconfiguration models vary in degree, they often require an economic effort at the development stage. Flexibility is considered key in determining efficient demand management, and, it has been seen as a means to manage peak demand and to address a certain amount of volume flexibility [ 28 ].…”
Section: Theoretical Considerations: Flexible Responses In An Ever-ch...mentioning
confidence: 99%